2017
DOI: 10.3390/ijms18020438
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Remote Ischemic Preconditioning on Heme Oxygenase-1 Expression and Cutaneous Wound Repair

Abstract: Skin wounds may lead to scar formation and impaired functionality. Remote ischemic preconditioning (RIPC) can induce the anti-inflammatory enzyme heme oxygenase-1 (HO-1) and protect against tissue injury. We aim to improve cutaneous wound repair by RIPC treatment via induction of HO-1. RIPC was applied to HO-1-luc transgenic mice and HO-1 promoter activity and mRNA expression in skin and several other organs were determined in real-time. In parallel, RIPC was applied directly or 24h prior to excisional woundin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Some pathogens and microvascular clotting, vasoconstriction, and molecules released in the context of tissue damage can influence lyses and concomitant Hb leakage into plasma [31]. Probably the upregulation of heme oxygenase described in several studies confirms heme degradation under RIPC conditions [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some pathogens and microvascular clotting, vasoconstriction, and molecules released in the context of tissue damage can influence lyses and concomitant Hb leakage into plasma [31]. Probably the upregulation of heme oxygenase described in several studies confirms heme degradation under RIPC conditions [4].…”
Section: Discussionmentioning
confidence: 99%
“…According to Kolh [3] the protective actions of IPC are dependent on the type of organ and applied ischemic preconditioning protocol. Regardless of that, the changes caused by ischaemia start at the molecular level: it changes the activation of some genes, post-transcriptional modification of mRNA, and protein activity in the cells [3, 4]. It has been shown that IPC induces changes in genes expression.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An elegant approach to analyze HO-1 expression in different organs due to RIC was done by Cremers et al measuring HO-1 promotor activity and HO-1 mRNA in HO-1 luc transgenic mice [144]. These mice carry a transgene consisting of the full-length mouse HO-1 promotor fused to the reporter gene luciferase (luc).…”
Section: The Role Of Remote Ischemic Conditioning On Ho-1 Modulationmentioning
confidence: 99%